Weight Change and Mortality Risk in Heart Failure With Preserved Ejection Fraction - Huang, Peisen; Guo, Zejun; Liang, Weihao; Wu, Yuzhong; Zhao, Jingjing; He, Xin; Zhu, Wengen; Liu, Chen; Dong, Yugang; Yu, Yuan; Dong, Bin (Frontiers in Cardiovascular Medicine, 2021)
Aims: To determine the associations of weight loss or gain with all-cause mortality risk in heart failure with preserved ejection fraction (HFpEF). Methods and results: Non-lean patients from the Americas from the Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist study were analyzed (n=1515). Weight loss and weight gain were defined as a decrease or increase of weight ≥5% between baseline and 1-year. To determine the associations of weight change and mortality risk, we used adjusted Cox proportional hazards models and restricted cubic spline models. The mean age was 71.5 (9.6) years. Weight loss and gain were witnessed in 19.3% and 15.9% patients, respectively. After multivariable adjustment, weight loss was associated with higher risk of mortality (HR 1.42, 95% CI 1.06-1.89, P = 0.002); weight gain had similar risk of mortality (HR 0.98, 95% CI 0.68-1.42, P = 0.932) compared with weight stability. There was linear relationship between weight change and mortality risk. The association of weight loss and mortality was different for patients with and without diabetes mellitus (interaction p=0.009). Conclusion: Among patients with HFpEF, weight loss was independently associated with higher risk of all-cause mortality, and weight gain was not associated with better survival.